Study of Partial Substitution Levels of Wheat Flour with Purple Sweet Potato Puree on Qualities of Brownies - Hongpan, Nawaporn; Chainarong, Kanyarat; Kalawong, Soontreeya (Burapha Science Journal, 2026)
The objective of this research was to study the suitable basic formula of brownie products by evaluating the sensory characteristics using a 9-points hedonic scale. The results showed that the basic formula2 had higher liking scores of all sensory characteristics than other formulas. The main ingredients of the optimum basic formulation of brownie products contained wheat flour, sugar, unsalted butter, cocoa powder, eggs, vanilla extract, baking powder and salt. Therefore, the basic formula2 was selected to study the optimum level of wheat flour replacement with the purple sweet potato puree. The results showed that the optimum replacement level for wheat flour with 50% purple sweet potato puree gave the crust and crumb color of brownies in dark brown and purple tones. The result found that hardness (2232.9 g), cohesiveness (0.35), springiness (0.55 mm), adhesiveness (-33.12 g.sec.), gumminess (1105.9 g), chewiness (656.26 g.mm), water content 0.70, moisture content 14.91%, specific volume (1.19 cm3/g.) and dietary fiber (4.03%). The brownies with 50% purple sweet potato puree had the highest overall preference score at 7.63.